High school students’ use of digital technology as a predictor of measures of academic progress - Marshall, Dylan D. (Animo Repository, 2012)
Digital technology is widely used by tech-savvy ‘digital native’ students in their learning. Research shows that this can have both positive effects, no effects and also negative effects on academic attainment. This study investigated whether high school students’ use of digital technology in their learning positively predicted their academic attainment. Students use of digital technology was measured using the Tech-savvy Scale (α=.91) which consists of three factors, connection, adaptation and control. Academic attainment was measured using students Measures of Academic Progress (MAP) scores in math, language and reading (α=.74). Participants were 218 international school students of mixed gender and ethnicity aged between 15 and 17 years. The data were analyzed using structural equation modeling (SEM) and the proposed model had a fair fit (RMSEA .08; CFI .97). When taken as one factor, Tech-savvy scale score did not predict academic attainment (p>0.05). However, the connection factor of the Tech-savvy Scale positively predicted academic attainment in language (p<0.05) and the control factor negatively predicted academic attainment in language and reading (p<0.05). Results are discussed in light of the conflicting previous research, and have implications in understanding the complex of the relationship between use of digital technology and their academic attainment.